Correlation Between Axial Length And Melatonin Serum Levels (Mel) In Teenagers With Myopia: Oral Presentation - Observational Study - Resident - sefira dwi ramadhany; Fithria Aldy; Aryani Atiyatul Amra (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : To determine correlation between axial length and melatonin serum levels (mel) in teenagers with myopia Methods : This research is an analytic observational with a case control design. A total of 52 subjects with myopia eyes in the study and control group. Results : The average melatonin level in the case group was 179.67 pg/mL (SD = 146.48 pg/mL) in the control group, the average was 111.56 pg/mL (SD = 48.72 pg/mL). Melatonin levels were highest in the group of subjects with severe myopia with an average of 250.36 pg/mL (SD = 304.89), moderate myopia with an average of 188.93 pg / mL (SD = 131 pg/mL), and the lowest melatonin levels in the emmetropic group with a mean of 111.56 pg/mL (SD = 48.72 pg/mL). Using the Kruskal Wallis test showed that there were differences in melatonin levels based on the degree of myopia (p = 0.278). Melatonin levels differed significantly between emmetropic subjects with mild myopia (p = 0.014), moderate myopia (p = 0.012). However, there was no difference in melatonin levels between subjects with emmetropia and severe myopia (p = 0.338) Conclusion : There was no significant correlation between melatonin levels and axial length (p = 0.401) and the degree of myopia (p = 0.055)